Corporate Social Responsibility and Corporate Governance: New Dimensions - Ramachandran, R. (Prabandhan: Indian Journal of Management, 2010)
Today’s heightened interest in the role of businesses in society has been promoted by increased sensitivity to, and awareness of environmental and ethical issues. Issues like environmental damage, improper treatment of workers, and faulty production leading to customers’ inconvenience or danger, are highlighted in the media. In some nations, government regulations regarding environmental and social issues has increased, and standards and laws are also often set at a supranational level. It forces many corporation’s Corporate Social Responsibility (CSR) policy in making decisions. Some consumers have become increasingly sensitive to the CSR performance of the companies from which they buy their goods and services. These trends have contributed to the pressure on companies to operate in an economically, socially and environmentally sustainable way. CSR is the way for remedy and which is the continuing commitment by business to behave ethically and contribute to economic development while improving the quality of life of the workforce and their families as well as of the local community and society at large. This holistic approach to business regards organizations as being full partners in their communities, rather than seeing them more narrowly as being primarily to make profits and serve the needs of their shareholders. CSR goes beyond charity and requires that a responsible company takes into full account their impact on all stakeholders and on the environment when making decisions. This requires them to balance the needs of all stakeholders with their need to make a profit, and reward their shareholders adequately. Some nations require CSR reporting, though agreement on meaningful measurements of social and environmental performance is difficult. Many organizations now produce externally, annual reports that cover sustainable development and CSR issues, but the reports vary widely in operations and evaluation methodology.